Spillover Effects of Early-Life Medical Interventions - Daysal, N. Meltem; Simonsen, Marianne; Trandafir, Mircea; Breining, Sanni (The Review of Economics and Statistics, 2022)
We investigate the effects of early-life medical treatments on the treated children and their families. We use a regression discontinuity design that exploits changes in medical treatments across the very low birth weight (VLBW) cutoff. Using administrative data from Denmark, we establish that VLBW children have better health and higher test scores. We find that these benefits spill over to other family members: mothers enjoy better mental health, and siblings have higher test scores. Maternal mental health improvements seem to be driven by better focal child health and sibling spillovers by improved interactions within the family and parental compensating behavior.